Efficient Microfluidic Power Generator Based on Interaction between DI Water and Hydrophobic-Channel Surface - Choi, Yong Whan; Jang, Segeun; Chun, Myung-Suk; Kim, Sang Moon; Choi, Mansoo (International Journal of Precision Engineering and Manufacturing-Green Technology, 5(2), 2018)
The fabrication of power generators utilized by streaming potential has been attracting profound interests for various applications such as wearable healthcare and self-powered micro/nano systems. So far, streaming potential has been generated by a charged channel wall and accumulated counter-ions. However, this approach is assumed as no-slip boundary condition, while the slippery channel wall is critical for high efficiency. Herein, we demonstrate a microfluidic power generator based on streaming potential that can be intrinsically charged at a hydrophobic channel wall. This charging mechanism has higher values of charge density and slip boundary condition. We have achieved output voltage of ~2.7 V and streaming conductance density of ~1.23 A/m 2 ·bar with the channel that is ~2 μm high and ~3.5 μm wide. Our result is a promising step for obtaining low-cost, high efficient power-generators for micro/nano systems.